PROBLEMS OF OLYMPIC EDUCATION AND ITS INTEGRATION INTO THE EDUCATIONAL SYSTEM (Physical Culture and Sport: Scientific Perspective, 2025)
The Olympic movement is one of the largest socio-cultural phenomena of our time, combining the traditions of antiquity and current globalization processes. Olympic education plays an important role in popularizing a healthy lifestyle and shaping the value orientations of young people, and its integration into the Ukrainian education system will help to increase physical activity and foster moral and ethical principles.The article analyzes the main internal and external problems that hinder the effective development of Olympism and Olympic education. Five key challenges are identified: 1. Insufficient level of Olympic education combined with a high interest in its implementation among teachers and students; 2. Commercialization of the Olympic Games, which leads to the devaluation of their ideological foundations; 3. Contradictions between sports activities and ethical standards; 4. Low effectiveness of existing institutions engaged in the development of Olympic education; 5. Difficulties in attracting young people to the ideals of Olympism. While the first and last problems are the subject of discussions and attempts to solve them, other aspects remain insufficiently studied. The article proposes approaches to optimizing the implementation of Olympic education in Ukraine, in particular through prioritizing its content.  The author emphasizes the need to adapt the materials in accordance with the age characteristics of students: for primary school age, it is advisable to use fairy-tale and game forms, for secondary school age - an emphasis on justice, and for high school and university students - motivational aspects of achieving life goals. It is proposed to limit the excessive theorization of the Olympic education course and focus on the practical component, which includes the organization of the Small Olympic Games as the culmination of the educational process. Practical mastery of Olympic values should be accompanied by an awareness of such fundamental categories as peace, social responsibility, patriotism, healthy lifestyle and environmental culture.
Keywords: Olympic Games; Olympism; Olympic education; Olympic sport; Olympic movement; integration; problems